Communicating with people on the job - Fulginiti, Tony; Communication Briefing (Blackwood, N.J. : Communication Briefing, 1991)
This video will help you become the most effective person-to-person communicator in your organization.
Presenter: Tony Fulginiti
Keywords: Communication in business; Interpersonal relations